EXPERIMENTAL STUDY OF LONG-TERM OUTCOMES OF PERINATAL USE OF DRUGS FOR PROGENY HEALTH - A.G. Reznikov; N.D. Nosenko (Bukovynian State Medical University, 2019)
Results of own experimental studies of long-term outcomes of perinatal use of certain drugs for progeny health were summarized in this work. It has been shown that the use of calcium channel blockers or glucocorticoids in critical periods of organism development was an important factor of formation of functional disorders of reproduction and adaptation systems as well as, the sexual behavior in remote periods of life. These data support the concept of risk of undesirable long-term outcomes of the early use of certain drugs for the reproductive health and adaptation potential of adult progeny.